2005
DOI: 10.1093/occmed/kqi195
|View full text |Cite
|
Sign up to set email alerts
|

Work ability of workers in western China: reference data

Abstract: WAI is validated in Chinese occupational practices. Some reference data are different from Finnish data. This study provides gender, age and work-content-specific WAI reference values that will help enable comparison and intervention evaluation in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 8 publications
2
24
1
5
Order By: Relevance
“…In that study, the sample was younger (mean age 42, vs 48 years in the present study), which is a plausible explanation for the higher observed work ability. In comparison, healthy workers rated their current work ability on average at 88 % [56] and 79 % [57], which was, after being transformed to a 0–10 scale, 1.7 and 0.8 point higher than the work ability reported in our study. The rates of work performance observed in our study were in accordance with the results of Bernaards et al [58], who also used the HPQ in workers with neck and upper limb symptoms, and others [4, 12].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In that study, the sample was younger (mean age 42, vs 48 years in the present study), which is a plausible explanation for the higher observed work ability. In comparison, healthy workers rated their current work ability on average at 88 % [56] and 79 % [57], which was, after being transformed to a 0–10 scale, 1.7 and 0.8 point higher than the work ability reported in our study. The rates of work performance observed in our study were in accordance with the results of Bernaards et al [58], who also used the HPQ in workers with neck and upper limb symptoms, and others [4, 12].…”
Section: Discussionmentioning
confidence: 64%
“…Secondly, because of the cross-sectional data collection, no causal inferences could be made. Thirdly, comparison of work ability measured on a 0–10 scale with reference values of the WAI was performed after transformation of average WAI-scores into a percentage [56, 57]. Therefore, the reference values are an indication and should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies, 8, 16 we classified these occupations into one of four categories: (1) manual worker (general labor), (2) professional and clerical (professional, business, clerical, health profession), (3) Semi-skilled professional (policy/military, farmer, skilled labor), and (4) other ( self-employed, homemaker, other). 8, 16 In regards to the homemaker category, these were patients who identified as currently working for pay and working at least 35 hours a week, but indicated their primary/main job as “homemakers”. The VIRGO study also ascertains reasons why patients stopped working at 12 months, including: (1) fired/lost job, (2) prefer not to work, and (3) no longer able to work.…”
Section: Methodsmentioning
confidence: 99%
“…근로자의 작업능력은 여러 가지 요인에 의해서 영향을 받는다고 기존 연구를 통해 제시되고 있다 [3,4,5,6,7]. 많 은 연구에서 근로자의 작업능력에 영향을 미치는 요인으로 직무스트레스를 제시하고 있다 [8,9,10,11].…”
Section: 연구의 배경 및 목적unclassified